A self-supervised, physics-aware, Bayesian neural network architecture for modelling galaxy emission-line kinematics. Issue 1 (13th February 2021) - Dawson, James M; Davis, Timothy A; Gomez, Edward L; Schock, Justus
ABSTRACT: In the upcoming decades, large facilities, such as the SKA, will provide resolved observations of the kinematics of millions of galaxies. In order to assist in the timely exploitation of these vast data sets, we explore the use of a self-supervised, physics-aware neural network capable of Bayesian kinematic modelling of galaxies. We demonstrate the network's ability to model the kinematics of cold gas in galaxies with an emphasis on recovering physical parameters and accompanying modelling errors. The model is able to recover rotation curves, inclinations and disc scale lengths for both CO and H i data which match well with those found in the literature. The model is also able to provide modelling errors over learned parameters, thanks to the application of quasi-Bayesian Monte Carlo dropout. This work shows the promising use of machine learning, and in particular, self-supervised neural networks, in the context of kinematically modelling galaxies. This work represents the first steps in applying such models for kinematic fitting and we propose that variants of our model would seem especially suitable for enabling emission-line science from upcoming surveys with e.g. the SKA, allowing fast exploitation of these large data sets.